Tren Global Emisi Dinitrogen Oksida dari Pemupukan NPK: Tinjauan Sistematis dan Analisis Bibliometrik - Anggi Diyah Ayu Oka; Anis Tatik Maryani; Zainul Bahri; Samsul Ma’arif (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the development, distribution, and scientific structure of research related to the use of NPK fertilizers and nitrous oxide (N₂O) emissions in the last decade. The increased use of nitrogen fertilizers in modern agricultural systems has contributed to greenhouse gas emissions, especially nitrous oxide (N₂O), which has a high global warming potential. This study uses a Systematic Literature Review (SLR) approach combined with a bibliometric analysis based on Scopus data for the 2015-2025 period. The literature selection process was carried out using PRISMA guidelines, resulting in 114 articles that were further analyzed using VOSviewer software. The results of the study show that publications increased significantly after 2020, with research dominated by Chinese and Asian-based institutions. Keyword analysis shows that research is still dominated by soil geochemical approaches, while integration with aspects of nitrogen use efficiency, crop productivity, and climate change mitigation is still limited. In addition, the collaboration network shows fragmentation between research groups. Overall, this study reveals conceptual and geographic gaps in research and emphasizes the importance of developing an integrative approach to fertilizer management and supporting sustainable agriculture and greenhouse gas mitigation.